2022
DOI: 10.21608/ejhm.2022.258687
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Methotrexate on Cerebellar Cortex: Review Article

Abstract: Background: Cerebellum, also known as the "small brain," is a highly stereotypical cortical structure located in the vertebrate hindbrain. Its primary function is to aid in motor control, but it also processes a wide range of sensory functions. Methotrexate (MTX) is widely used as a chemotherapy agent for treating many different kinds of cancer. Psoriasis, SLE, IBD, vasculitis, and a wide variety of other connective tissue illnesses can all benefit from it without any negative side effects. The neurological sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…Our findings are consistent with previously published studies that reported a decline in hippocampal neurogenesis, resulting in memory deficits and cognitive impairment following MTX administration [13,14,40]. Obviously, it is well known that MTX adversely affects other brain regions, including the cerebellum and cerebral cortex, causing various neurotoxic effects and leukoencephalopathy [41][42][43]. However, these regions are not widely known to be implicated in memory and learning behaviors.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with previously published studies that reported a decline in hippocampal neurogenesis, resulting in memory deficits and cognitive impairment following MTX administration [13,14,40]. Obviously, it is well known that MTX adversely affects other brain regions, including the cerebellum and cerebral cortex, causing various neurotoxic effects and leukoencephalopathy [41][42][43]. However, these regions are not widely known to be implicated in memory and learning behaviors.…”
Section: Discussionsupporting
confidence: 93%